Prove (a-b)²=a²-2ab+b²


Because (a-b)² is area of just 4th part of total area. When we calculate the area of 4th part, we just deduct 1st part’s area, 2nd part’s area and 3rd part’s area from total area of any square.


More Like This

Leave a Reply

Your email address will not be published. Required fields are marked *

You may use these HTML tags and attributes: <a href="" title=""> <abbr title=""> <acronym title=""> <b> <blockquote cite=""> <cite> <code> <del datetime=""> <em> <i> <q cite=""> <strike> <strong>